Genetic Monitoring of Crimean-Congo Hemorrhagic Fever Virus in the South of the European Part of Russia - A. S. Volynkina; A. N. Kulichenko (Проблемы особо опасных инфекций, 2012)
Presented are the results of gene-typing of CCHF virus detected in clinical samples from CHF patients from the Stavropol, Rostov and Astrakhan Regions in 2011. For 28 samples determined are nucleotide sequences of the fragments 115–652 (S segment) and fragments 984–1469 (M segment). Philogenetic analysis of these nucleotide sequences demonstrated that typical strains circulated in 2011 in the regions under surveillance, importation of the new genetic variants of the virus did not take place. CCHF virus variant affiliated to the subgroup “Astrakhan-2” was detected in the clinical samples for the first time and characterized for its genome S- and M-segment fragments.